Blue Carbon: Integrative Management of Coastal Ecosystems Based on Regional Autonomy - Anwar, Muhammad Syaiful; Ruhtiani, Maya; Hendriana, Rani (Jambe Law Journal, 2023)
Coastal ecosystems are unlimited natural resources owned by archipelagic countries. The division of management of coastal areas in the use of blue carbon between the central government and regional governments based on regional autonomy needs special attention. The article implies a strategy that recognizes the importance of coastal ecosystems, particularly in blue carbon sequestration, and advocates for a comprehensive and decentralized management approach that considers the unique characteristics and needs of different regions. This approach aligns with the concept of regional autonomy, emphasizing the involvement of local authorities in decision-making processes related to the management of coastal ecosystems. The focus of this article is to determine the urgency for the state to have absolute control over coastal areas in utilizing blue carbon based on regional autonomy and to determine the extent to which the pattern of sustainable blue carbon policy management in coastal areas is a form of state accountability. This article shows that regional government participation in blue carbon management in coastal areas must be done based on their restricted autonomy rights, a systematic and structured sustainable, integrative policy pattern in environmental management as a form of environmental protection.